Applications of Magnetic Particle Imaging in Biomedicine: Advancements and Prospects - Yang, Xue; Shao, Guoqing; Zhang, Yanyan; Wang, Wei; Qi, Yu; Han, Shuai; Li, Hongjun (Frontiers in Physiology, 2022)
Magnetic particle imaging (MPI) is a novel emerging noninvasive, radiation-free imaging modality that can quantify superparamagnetic iron oxide nanoparticles (SPIONs) tracers. The zero endogenous tissue background signal and short image scanning times ensure the high spatial and temporal resolution of MPI. In the current study, after a brief explanation of the principle of MPI and the development involving system, as well as tracer, we mainly focus on the recent advancements in the biomedical application of MPI, including vascular structure and perfusion imaging, cancer imaging, MPI guidance of magnetic fluid hyperthermia, and visual monitoring of cell and drug treatment, intraoperative navigation. Finally, we present the optimization of MPI at the aspect of system and tracers, as well as the potential biomedical applications of MPI in the future. In the context of precision medicine, the advantages of MPI can provide a new strategy for the integration of diagnosis and treatment of diseases.